2001
DOI: 10.1007/s00417-001-0379-1
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortins are comparable to corticosteroids as inhibitors of traumatic ocular inflammation in rabbits

Abstract: We demonstrated that MSH reduced the clinical signs of ocular inflammation, curtailed blood-aqueous barrier (BAB) disruption, and reduced aqueous inflammatory cell number. The efficacy of MSH applied systemically or topically was similar to that of steroids in reducing clinical signs of trauma, but MSH efficacy in maintaining BAB integrity surpassed that of steroids. We suggest that the melanocortins might be a useful anti-inflammatory agents in ocular trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…2 Furthermore, ␣-MSH has a potent anti-inflammatory action in brain inflammation, 3 renal injury, 4 and liver inflammation experimental models. 5 Other reports 6,7 of studies that have used the rabbit eye inflammation model, have found that ␣-MSH reduces blood-aqueous barrier failure and infiltration of inflammatory cells into the aqueous humor. One of the anti-inflammatory activities of MSH is reported to be the suppression of NF-B activation.…”
mentioning
confidence: 99%
“…2 Furthermore, ␣-MSH has a potent anti-inflammatory action in brain inflammation, 3 renal injury, 4 and liver inflammation experimental models. 5 Other reports 6,7 of studies that have used the rabbit eye inflammation model, have found that ␣-MSH reduces blood-aqueous barrier failure and infiltration of inflammatory cells into the aqueous humor. One of the anti-inflammatory activities of MSH is reported to be the suppression of NF-B activation.…”
mentioning
confidence: 99%
“…Examples of such effects are suppression of pro-inflammatory cytokines production (interferon-γ, tissue necrosis factor-α, IL-1, and IL-8), induction of cytokine suppressors (IL-10), inhibition of expression of intercellular adhesion molecules and modulation of lymphocytes activity and proliferation 24 . The anti-inflammatory effects of α-MSH have been demonstrated in a variety of animal models, such as mice, rabbits, and rats 27, 28, 29…”
Section: Discussionmentioning
confidence: 99%
“…The effects can be dramatic and systemic 33 . For example, Naveh and Marshall investigated the anti-inflammatory effect of melanocyte-stimulating hormone (MSH), which is a known anti-inflammatory agent, after ocular surgery 34 . Additionally, halothane was found to inhibit red blood cell and liver G6PD enzyme activities significantly in the first week and to activate this enzyme in the second week of anesthesia compared with a control group 35 .…”
Section: Discussionmentioning
confidence: 99%